Interpretation of experimental results on Kondo systems with crystal field - Romero, M.A.; Aligia, A.A.; Sereni, J.G.; Nieva, G.; Sereni, Julián; Nieva, Gladys (IOP Publishing, 2014)
Fil: Aligia, A.A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina